HAKIKAT PENDIDIK DALAM PENDIDIKAN ISLAM - Abdul Haris; Mokh. Fakhruddin Siswopranoto (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2022)
Educators are people who get a mandate and have the responsibility of the hereafter in educating, guiding, directing and delivering students to the happiness of the world and the hereafter. Therefore, to become a qualified and professional educator, one must have certain criteria and requirements that must be met in order to achieve the goals of life, as well as the characteristics that adorn his personality in carrying out his duties and responsibilities as educators in the view of Islam. pay attention to their duties and responsibilities towards students, which are based on faith and piety to Allah SWT and are able to develop the potential that exists both physically and mentally (physically, psychologically, and spiritually). For this reason, an educator is required to have strong faith and piety, strong and sincere intentions based on Islamic teachings and decorated with morality.